INTEGRATING THE HEXA HELIX MODEL, ECOTOURISM, AND LOCAL WISDOM FOR SUSTAINABLE TOURISM A LITERATURE REVIEW - Wayan Ardani; Anak Agung Elik Astari; Ni Luh Ketut Ayu Sudha Sucandrawati; I Kadek Donny Wishanesta; I Made Agus Mahendra (Jurnal Ilmiah Vastuwidya, 2026)
Sustainable tourism is a strategic approach to address the challenges of environmental degradation, cultural preservation, and empowering local communities. This study aims to examine the role of the Hexa Helix collaborative model, local wisdom, and ecotourism in supporting sustainable tourism development.  This model is hindered by the absence of comprehensive frameworks, characterized by disjointed research across disciplines and limited long-term impact evaluations. Common issues include inadequate stakeholder coordination, resource constraints, insufficient community preparedness, and insufficiently examined cultural-ecological linkages. Literature reviews synthesize fragmented studies on Hexa Helix, local wisdom, and ecotourism to identify gaps such as coordination barriers and the necessity for theoretical advancement. They enable holistic frameworks for directing policy for tourism sustainable development. The study was conducted through a Systematic Literature Review (SLR) of scientific journals, policy reports, and case studies between 2015 and 2025 search through google scholar. The selection of the 50 most related to the variables of research was acquired to provide a more accurate analysis. This study revealed that the success of sustainable tourism is greatly influenced by the collaboration of Hexa Helix actors integrated with the principles of local wisdom and ecotourism, especially in destination management, strengthening local capacity, and digital-based promotion and environmental ethics. Local wisdom serves as a foundation for cultural values and identity that enrich destination narratives, increase local community involvement, and maintain environmental sustainability and cultural heritage. This study can be as reference that the integrative model of Hexa Helix, local wisdom, and ecotourism as a transformative strategy in developing inclusive, adaptive, and sustainable Indonesian tourism.